A Low‐Swelling Polymeric Mixed Conductor Operating in Aqueous Electrolytes. Issue 2 (30th November 2020) - Nicolini, Tommaso; Surgailis, Jokubas; Savva, Achilleas; Scaccabarozzi, Alberto D.; Nakar, Rana; Thuau, Damien; Wantz, Guillaume; Richter, Lee J.; Dautel, Olivier; Hadziioannou, Georges; Stingelin, Natalie
Abstract: Organic mixed conductors find use in batteries, bioelectronics technologies, neuromorphic computing, and sensing. While great progress has been achieved, polymer‐based mixed conductors frequently experience significant volumetric changes during ion uptake/rejection, i.e., during doping/de‐doping and charging/discharging. Although ion dynamics may be enhanced in expanded networks, these volumetric changes can have undesirable consequences, e.g., negatively affecting hole/electron conduction and severely shortening device lifetime. Here, the authors present a new material poly[3‐(6‐hydroxy)hexylthiophene] (P3HHT) that is able to transport ions and electrons/holes, as tested in electrochemical absorption spectroscopy and organic electrochemical transistors, and that exhibits low swelling, attributed to the hydroxylated alkyl side‐chain functionalization. P3HHT displays a thickness change upon passive swelling of only +2.5%, compared to +90% observed for the ubiquitous poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate, and +10 to +15% for polymers such as poly(2‐(3, 3′‐bis(2‐(2‐(2‐methoxyethoxy)ethoxy)ethoxy)‐[2, 2′‐bithiophen]‐5‐yl)thieno[3, 2‐b]thiophene) (p[g2T‐TT]). Applying a bias pulse during swelling, this discrepancy becomes even more pronounced, with the thickness of P3HHT films changing by <10% while that of p(g2T‐TT) structures increases by +75 to +80%. Importantly, the initial P3HHT film thickness is essentially restored after de‐doping while p(g2T‐TT) remains substantially swollen. The authors, thus, expand the materials‐design toolbox for the creation of low‐swelling soft mixed conductors with tailored properties and applications in bioelectronics and beyond. Abstract : Although beneficial to ion transport, swelling can affect the performance and durability of organic mixed conductor devices. A hydrophilic conjugated polymer, poly[3‐(6‐hydroxy)hexylthiophene] is presented, and its swelling properties are compared to state‐of‐the‐art glycolated organic semiconductors for bioelectronics. Hydroxyl functionalization of poly(thiophene) backbone minimizes swelling while still allowing good ion uptake, resulting in robust organic electrochemical transistor operation in aqueous electrolytes.